The influence of lithology and tectonics on the development of the karst landscape in the Dong Van Global Geopark, NE Vietnam - Doan, Manh Ha; Gałka, Elżbieta (Geotourism/Geoturystyka, 2020)
The Dong Van Karst Plateau Geopark is located in the mountainous area of the northern part of Vietnam. It became the 77th member of the Global Geoparks Network in 2010. The Dong Van Karst Plateau Geopark is a unique combination of breathtaking scenery and culture of ethnic groups, with many potential values such as its geoheritage, biological diversity and historical places, which attract many domestic and foreign visitors. Up to 60% of the area of this geopark is covered by karst. Its topography is strongly dissected by deep river gorges with steep slopes, and this area has experienced several deformational phases from the Middle Cambrian/Early Ordovician, to the Cenozoic. These elements contributed to the breathtaking scenery of the Dong Van Karst Plateau Geopark, the first global geopark in Vietnam and the second in South-East Asia.